The evaluation of three diagnostic tests for the detection of equine influenza nucleoprotein in nasal swabs. Issue 3 (7th February 2014) - Galvin, Pamela; Gildea, Sarah; Nelly, Maura; Quinlivan, Michelle; Arkins, Sean; Walsh, Cathal; Cullinane, Ann
<x xml:space="preserve">Abstract</x> Background Equine influenza (EI) is a highly contagious respiratory disease of horses. Objectives The aim of this study was to evaluate two rapid antigen detection kits (Directigen or DFA, and Espline) and a commercial ELISA for the detection of EI nucleoprotein in nasal swabs. Method Nasal swab samples from naturally and experimentally infected horses were used to compare the sensitivity and specificity of these assays to virus isolation (VI) and real‐time RT‐PCR. Results If real‐time RT‐PCR was considered as the gold standard, the sensitivity of the other tests in field samples was 68% (DFA), 35% (ELISA), 29% (Espline), and 9% (VI). These tests had 100% specificity when compared to real‐time RT‐PCR. A receiver operating characteristic (ROC) curve indicated that decreasing the cutoff of the ELISA would increase sensitivity with some loss of specificity. In samples from experimentally infected horses, the sensitivity of the tests compared with real‐time RT‐PCR was 69% (VI), 27% (DFA), 6% (Espline), and 2% (ELISA). The specificity was 100% for Espline and ELISA and 95% for VI and DFA. Conclusions This study illustrated that DFA is the most sensitive antigen detection test evaluated for the diagnosis of EI and that it can detect virus in some subclinical infected and vaccinated horses. The results suggest that DFA is a useful adjunct to laboratory tests and may be effective as a screening test in a quarantine station or similar facility where horses are monitored daily.